PENGARUH VARIASI KONSENTRASI DAN LAMA PERENDAMAN ASAM LAKTAT TERHADAP KADAR GLUKOSA DAN KUALITAS TEPUNG UBI JALAR (Ipomoea batatas L) - Ruly Fitri Nurani (Florea : Jurnal Biologi dan Pembelajarannya, 2016)
Dependence on certain essential food commodities has led to the difficulty of overcoming  food availability. One of the food that has potential as a substitute for staple foods are sweet potatoes. The purpose of this study was to determine the effect of variations in the lactic acid concentration and soaking time on the glucose contant and quality sweet potato flour. The research is quantitative with RAL factorial 2 x 1 in 3 times repetition. The factor of research are variation of lactic acid concentration (0%, 0.5%, 1%, and 1.5%) and variation of lactic acid soaking time (30 minutes, 60 minutes, 90 minutes).Research use titration Na-tiosulfat to collect the data of glucose contant. Anava two tail is used to examine the hypothesis continued with BNJ examination. The result of hypothesis shows that sig t (variation of lactic acid concentration and variation of lactic acid soaking time) for glucose contant in sweet potato flour 0,000 with significance degree 0,05. From result above, the conclusion is variation of lactic acid concentration and variation of lactic acid soaking time affect the glucose contant and quality sweet potato flour.